Penerapan Pasal 106 Ayat 1 UU NO.22 Tahun 2009 Dengan Menggunakan ETLE - Saepuloh, Muhamad; Kusumah, Haidan Angga (Ilmu Hukum Prima (IHP), 2024)
Traffic is a crucial part of public mobility, allowing people to move from one point to another, and also plays a significant role in economic growth, including both human and goods transport services. With the advancement of technology, however, transportation has also had adverse effects on human life, such as accidents that claim many lives. Therefore, the operation of motor vehicles is regulated by Law No. 22 of 2009 concerning road traffic and transportation. This regulation is now enforced not only manually but also through the ETLE electronic system, demonstrating that the police are also keeping pace with technological progress. The aim of this study is to examine whether the implementation of Article 106, paragraph 1, through the ETLE system is functioning effectively or, perhaps, otherwise.